2011
DOI: 10.1055/s-0031-1280756
|View full text |Cite
|
Sign up to set email alerts
|

Ergebnisqualität in der Kinder-Jugend-Rehabilitation: Resultate eines Projekts zur Entwicklung eines Qualitätssicherungsverfahrens

Abstract: The strengths of the instruments that were developed are that a scientifically demanding quality measurement was conducted (e. g., combination of indirect and direct measurement of change, several methodological approaches to measuring results, wide range of endpoints analysed, homogeneous comparison groups, elaborate risk adjustment process). There are limitations, especially with respect to the rather great effort needed and not particularly high power for the comparison of centres. The German pension fund a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
18
0
10

Year Published

2011
2011
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 12 publications
(30 citation statements)
references
References 11 publications
2
18
0
10
Order By: Relevance
“…The majority of the 18 included studies reported about rehabilitation programs from Germany [5,7,10,11,16,25,32,39,44,51]. The others were studies from the USA [4,29,38], Canada [27], Australia [8], Austria [23] and one transnational study that included patients from Germany, Austria and Switzerland [46].…”
Section: Characteristics Of the Studies And Rehabilitation Programsmentioning
confidence: 99%
See 1 more Smart Citation
“…The majority of the 18 included studies reported about rehabilitation programs from Germany [5,7,10,11,16,25,32,39,44,51]. The others were studies from the USA [4,29,38], Canada [27], Australia [8], Austria [23] and one transnational study that included patients from Germany, Austria and Switzerland [46].…”
Section: Characteristics Of the Studies And Rehabilitation Programsmentioning
confidence: 99%
“…Twelve studies were single-center-studies [4,7,8,16,23,25,27,32,38,39,51], while the other 6 studies were multicenter studies [44,11,29,. Fourteen studies were uncontrolled studies and the other 4 were non-randomized controlled studies [7,16,38,46].…”
Section: Characteristics Of the Studies And Rehabilitation Programsmentioning
confidence: 99%
“…Erste Umsetzungsschritte scheinen ab Sommer 2011 denkbar (vgl. auch [7]). Sollte das Verfahren in der jetzigen Fassung oder nur leicht modifiziert in die Routineversorgung integriert werden, dürften aus dem Programm dauerhaft informative Daten zur Effektivität der Rehabilitation, insbesondere auch im Zeitverlauf, zu ziehen sein.…”
Section: Wert 6 Wochen Nach Der Rehabilitationunclassified
“…Aufgrund der Konzeption des eingesetzten Fragebogens zum Krankheitsmanagement (Selbstbeurteilungsinstrument für Jugendliche) werden in der vorliegenden Untersuchung Ergebnisse von Rehabilitanden im Alter von 12 bis 22 Jahren dargestellt. Die Diff erenz in den Fallzahlen für die Diagnosegruppen Adipositas und Asthma bronchiale ist dadurch zu erklären, dass die Mehrzahl der in stationärer Rehabilitation befi ndlichen Kinder mit Asthma bronchiale unter 12 Jahre alt ist, die Mehrzahl der Rehabilitanden mit Adipositas hingegen 12 Jahre oder älter ist (s. auch [ 10 ] ). Weitere Informationen zu soziodemografi schen sowie medizinisch-psychologischen Daten der Stichprobe können • ▶ Tab.…”
Section: Stichprobeunclassified
“…In der hier vorgestellten Untersuchung wurde im Rahmen des Gesamtprojektes auch die gesundheitsbezogene Lebensqualität der Rehabilitanden erfasst. Es zeigte sich, dass bei Jugendlichen der Diagnosegruppe Adipositas bei Behandlungsbeginn im Vergleich zu Jugendlichen anderer Diagnosegruppen eine verminderte Lebensqualität vorlag [ 10 ] …”
unclassified